Epizootiological and Epidemiological Situation in Tularemia Natural Foci in the Territory of the Central Federal District of the Russian Federation from 1992 to 2011 - V. P. Popov; D. S. Orlov; V. E. Bezsmertny (Проблемы особо опасных инфекций, 2012)
Outlined is a brief characteristics on epizootic and epidemic activity of tularemia natural foci in the territory of the Central Federal district of the Russian Federation over a period of 1992–2012. Implementation of GIS-technologies has made it possible to design retrospective map of the sites of the district population infectioning in 2005, and to distinguish the regions that are of a great epidemic significance.